No association between garlic intake and risk of colorectal cancer - Meng, Shasha (2012)
BACKGROUND: Although experimental studies suggested beneficial role of garlic intake on colorectal carcinogenesis, limited prospective cohort studies have evaluated garlic intake in relation to colorectal cancer (CRC) incidence. METHODS: We followed 76,208 women in the Nurses’ Health Study and 45,592 men in the Health Professionals Follow-up Study for up to 24 years and examined garlic intake and garlic supplement use in relation to CRC risk. Information on garlic intake and supplement use was assessed using a validated food frequency questionnaire and a Cox proportional hazard regression model was used to estimate the multivariable hazard ratio (MV-HR) and 95% confidence intervals (95% CIs). RESULTS: We documented 2,368 (1,339 women and 1,029 men) incident CRC cases and found no association between garlic intake and CRC risk; the MV-HRs (95% CIs) associated with garlic (1 clove or 4 shakes per serving) intake ≥1/day compared with <1/month were 1.21 (0.94–1.57; p-trend=0.14) for women and 1.00 (0.71–1.42; p-trend=0.89) for men. The MV-HRs (95% CIs) of CRC for garlic supplement use, which was used in 6% of the participants in each study, were 0.72 (0.48–1.07) for women and 1.22 (0.83–1.78) for men. CONCLUSION: Our prospective data do not support an important role of garlic intake or garlic supplement use in colorectal carcinogenesis.